Seroepidemiology of Toxoplasma gondii amongst Pregnant Women in Jazan Province, Saudi Arabia - Hussein Aqeely; Eman K. El-Gayar; Darakhshan Perveen Khan; Abdullah Najmi; Ayesha Alvi; Ibrahim Bani; Mohamed Salih Mahfouz; Saif Elden Abdalla; Ibrahim M. Elhassan (Journal of Tropical Medicine)
Background. Toxoplasma gondii (T. gondii) is an obligate intracellular protozoan parasite of worldwide distribution. There is limited information about the seroprevalence of toxoplasmosis in the southern area of Saudi Arabia. The current study was carried out to determine the prevalence of T. gondii in pregnant women in Jazan province. Materials and Methods. The study was conducted between January and June 2013 and included 195 pregnant women, data on sociodemographic and predisposing factors were collected from each participant. Venous blood samples were collected following standard operating procedures. Serological analysis for latent toxoplasmosis (levels of IgG) and active toxoplasmosis (IgM) was done using Enzyme Linked Immunosorbent Assay (ELISA). Results. The overall seroprevalence of T. gondii in the study area was 24.1%. The seroprevalence of anti-Toxoplasma IgG was 20% (39 out of 195), whereas IgM seropositivity was 6.2% (12 out of 195). Only 4 pregnant women tested positive for both IgG and IgM. The highest IgG and IgM seroprevalence was among the study participants aged 35 to 39 years (13.5% and 35.1%, resp.). The seropositivity rate of T. gondii-specific antibodies was higher among pregnant women from the urban areas than those from rural communities (7.4% versus 0% and 21% versus 15.4% for IgM and IgG, resp.). Conclusions. The seroprevalence of T. gondii was high in pregnant woman in Jazan. The prevalence of toxoplasmosis increases with increase of age. Awareness health education program in Jazan needs to be maintained and developed to targeted pregnant women.